Growth of the complex borates YxRySc2+z(BO3)4 (R = Nd, Pr, x + y + z = 2) with huntite structure. Issue 8 (29th May 2017) - Kokh, A. E.; Kuznetsov, A. B.; Pestryakov, E. V.; Maillard, A.; Maillard, R.; Jobard, C.; Kononova, N. G.; Shevchenko, V. S.; Kragzhda, A. A.; Uralbekov, B.; Kokh, K. A.
Abstract : Bulk crystals of nonlinear optical materials NdYSB and PrYSB without striation defects were grown using novel LiBO2 –LiF flux. It was confirmed that introduction of Y atoms to the Nd(Pr)Sc3 (BO3 )4 stabilizes the R32 huntite‐type structure, like it was shown for YLSB crystals. Taken together with the presence of active Nd 3+ and Pr 3+ rates, the studied crystals are suggested as promising self frequency doubling materials. Abstract : Bulk crystals of new huntite type borates were grown by TSSG method using eutectic LiBO2 –LiF as a flux. Chemical composition, X‐ray diffraction, optical absorption and fluorescence spectra of the grown samples were studied.